Software, Sovereignty and the Post-Neoliberal Politics of Exit. (November 2021) - Smith, Harrison; Burrows, Roger
This paper examines the impact of neoreactionary (NRx) thinking – that of Curtis Yarvin, Nick Land, Peter Thiel and Patri Friedman in particular – on contemporary political debates manifest in 'architectures of exit'. We specifically focus on Urbit, as an NRx digital architecture that captures how post-neoliberal politics imagines notions of freedom and sovereignty through a micro-fracturing of nation-states into 'gov-corps'. We trace the development of NRx philosophy – and situate this within contemporary political and technological change to theorize the significance of exit manifest within the notion of 'dynamic geographies'. While technological programmes such as Urbit may never ultimately succeed, we argue that these, and other speculative investments such as 'seasteading', reflect broader post-neoliberal NRx imaginaries that were, perhaps, prefigured a quarter of a century ago in The Sovereign Individual.